1994
DOI: 10.1038/sc.1994.7
|View full text |Cite
|
Sign up to set email alerts
|

Total en bloc spondylectomy and circumspinal decompression for solitary spinal metastasis

Abstract: We have developed a new surgical technique, 'total en bloc spondylectomy' (TES), to treat a solitary metastasis in the thoracic or lumbar vertebra. This operation is designed as a local cure for the metastatic site and involves the radical resection of the affected vertebra with a wide margin. The spondylec tomy consists of two steps: en bloc laminectomy with posterior spinal instru ments for stabilisation (first step) and en bloc corporectomy and replacement using a vertebral prosthesis (second step) . TES ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 5 publications
1
116
0
8
Order By: Relevance
“…The authors of this study furthermore demonstrated median survival time after en bloc spondylectomy of more than 30 months and nearly 20% surviving more than 5 years. These findings underscore the results reported by Tomita et al who demonstrated median survival times in patients after en bloc resection of 38 months [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The authors of this study furthermore demonstrated median survival time after en bloc spondylectomy of more than 30 months and nearly 20% surviving more than 5 years. These findings underscore the results reported by Tomita et al who demonstrated median survival times in patients after en bloc resection of 38 months [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Based on these promising results, Tomita et al were the first to extend the surgical oncological concept of en bloc spondylectomy also to the treatment strategy of solitary spinal metastases of selected patients with specific tumor entities [33][34][35]. According to these studies, there is general consensus that indication for en bloc spondylectomy requires careful patient selection for which the following criteria might be helpful: (1) no underlying tumor type, which is considered to be a systemic disease, (2) tumor types that are known to be biologically favorable and to have a prolonged course (e.g., renal cell or mamma carcinoma), (3) radical treatment of the original/primary tumor, (4) long period between treatment of primary tumor and diagnosis of solitary metastatic disease, and (5) cation of isolated/solitary metastatic disease in CT scans, bone scan and/or PET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described techniques were modified [7,32,37,58,59], prognostic surgical scores [56,57,60,61] were established considering the underlying tumor biology, the number/presence of extraspinal metastases and an estimation of life expectancy. With the results of these scores and the tremendous advance in spine surgery technique the indication from primary spinal tumors is now extended to selected cases of solitary spinal metastases with biologically favorable tumor entities [1,54,62,70]. Thanks to advances in tumor screening and diagnostics, the number of patients who may benefit from this extensive surgical treatment continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…This is the ®rst report of congenital kyphosis corrected using a total en-bloc spondylectomy. 7,8 Case report…”
Section: Introductionmentioning
confidence: 99%